Refractive Error Among School Going Children in Solukhumbu, Nepal - Sherpa, Ang Tshering Lama; Sherpa, Mingmar Gyalzen; Basnet, Pushpa Babu; Sherpa, Mingmar Chhiring (Nepalese Medical Journal, 2020)
Introduction: Reduced vision among school-going children is a global public health problem and uncorrected refractive error, the main causative factor is most prevalent in under-developed countries. Correction of refractive error can be easily done when diagnosed. Therefore regular eye health screening among school-going children and early correction is necessary to alleviate the problem and reduce its consequences. Materials and Methods: It was a retrospective cross-sectional stud and the data were retrieved from eye health screening camps conducted in different schools of Dudhkunda municipality in 2015 in collaboration with Solukhumbu Polytechnic Academy and District Community Eye Center Solukhumbu. Permission from respective authorities and ethical approval for the research was received from the institutional review committee of the Tilganga Institute of Ophthalmology. Out of 3097 records, 2517 records were analyzed to identify the prevalence of refractive error. Results: Age of the children ranged from 6 to 18 years and most of the children were studying in grade 1 to 7, from government school and janajatis. Most common eye disorder noted was refractive error and prevalence was 3.5% (87). Refractive error was higher among older children compared to younger children. Higher proportion of students from private schools had refractive error compared to students from government schools. Both the findings were statistically significant. Conclusions: Refractive error among school children in our study is lower than that of other studies conducted in Nepal and it may be due to the representation of younger age groups in our study.